Cross-sphere modelling to evaluate impacts of climate and land management changes on groundwater resources - Cochand, Fabien; Brunner, Philip; Hunkeler, Daniel; Rössler, Ale; Holzkämper, Annelie (My University, 2021)
Climate change affects both water resources and agricultural production.With rising temperatures and decreasing summer precipitation, it is expected that agricultural production will be increasingly limited by drought. Where surface- or groundwater resources are available for irrigation, an increase inwaterwithdrawals for irrigation is to be expected. Therefore, quantitative approaches are required to anticipate and manage the expected conflicts related to increased water abstraction for irrigation. This project aims to investigate how agricultural production,water demand for irrigation, runoff and groundwater dynamics are affected by future climate change and howclimate change impacts combinedwith changes in agriculturalwater use affect groundwater dynamics. To answer these research questions, a comprehensive, loosely coupled model approach was developed, combining models from three disciplines: an agricultural plant growth model, a hydrological model and a hydrogeological model. The model coupling was implemented and tested for an agricultural area located in Switzerland inwhich groundwater plays a significant role in providing irrigationwater. Our suggested modelling approach can be easily adapted to other areas. The model results show that yield changes are driven by drought limitations and rising temperatures. However, an increase in yieldmay be realized with an increase in irrigation. Simulation results showthat thewater requirement for irrigation without climate protection (RCP8.5) could increase by 40% by the end of the century with an unchanged growing season and by up to 80%with varietal adaptations. With climate changemitigation (RCP2.6) the increase inwater demand for irrigationwould be limited to 7%. The increase in irrigation (+12mm) and the summer decrease in recharge rates (~20mm/month)with decreasing summer precipitation causes a lowering of groundwater levels (40 mm) in the area in the late summer and autumn. This impact may be accentuated by an intensification of irrigation and reduced by extensification.
Keywords: Agriculture; Irrigation; Water resources; Water use conflict; Integrated modelling; Climate change